Delayed discharges at a major arterial centre: a 4-month cross-sectional study at a single specialist vascular surgery ward. Issue 9 (29th September 2016) - Houghton, J S M; Urriza Rodriguez, D; Weale, A R; Brooks, M J; Mitchell, D C
Abstract : Objectives: Delayed discharges are a significant problem for the National Health Service. The objectives of this study were to determine the prevalence and impact of delayed discharge at a single specialist vascular surgery ward. Design: A cross-sectional observational study. Setting: A single specialist vascular unit in the UK during a 4-month study period (01/09/2014–31/12/2014). Participants: All patients admitted to the ward during the study period were included. Patients spending ≥1 night on the ward once declared medically fit for discharge (MFFD) were prospectively identified and data prospectively collected. All other patients were identified retrospectively with data collected retrospectively from electronic records. Outcome measures: Primary outcome was number of patients experiencing delayed discharge. Secondary outcome measures were length of stay, length of delay and cost of delay. Results: There were 268 admissions with a total length of stay (LoS) of 2776 days. 57 admissions (21.3%) experienced delayed discharges with a total 535 excess bed days (19.3% total LoS) once MFFD. Unplanned admission (relative risk 7.3 (95% CI 2.7 to 20.0; p<0.001)) and index amputation (relative risk 9.2 (95% CI 3.8 to 22.0; p<0.001)) were associated with increased risk of delayed discharge. There were significant differences in the length of delay by the reason for the delay (p=0.01). Delay due to the provision of social services and inpatient rehabilitation were associated with longer length of delay (post hoc analysis). Age was not independently associated with either increased risk of delayed discharge or length of delay. The total estimated cost of delayed discharges during the study period was £146 055. Conclusions: A significant number of vascular patients experience delayed discharge. MFFD vascular patients occupy a high proportion of vascular beds at considerable financial cost. Unplanned admissions, amputees and those delayed due to social services contributed most to delays. Closer integration with community health and social care providers may reduce delays.